Pengaruh Pemberian Informasi tentang Asuhan Perkembangan pada BBLR terhadap Tingkat Pengetahuan dan Sikap Perawat di Rumah Sakit Al Islam Bandung - Yusi Sofiyah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Development care is an effort to modify the environment and respond to changes in the behavior of newborns, especially in infants Low Birth Weight, The purpose of this study was to determine the effect of training on developmental care on nurses' ability to care for babies with low birth weight. The design of this study used